The Gilgamesh epic in Genesis 1-11: peering into the deep - Miglio, Adam E. (Studies in the history of the ancient Near East, 2023)
This book provides a substantive, reliable, and accessible comparison of the Gilgamesh Epic and Genesis 1-11, investigating their presentation of humanistic themes such as wisdom, power, and the "good life". While the Gilgamesh Epic and Genesis 1-11 are characterized by historical and cultural features that may seem unusual or challenging to modern readers, such as the intervention of gods and goddesses and talking animals, these ancient literary masterpieces are nonetheless familiar and relatable stories through their humanistic composition. This volume explores the presentation of humanistic themes and motifs throughout both stories. Significant passages and narratives, such as stories from the Garden of Eden and the Flood, are translated into English and accompanied by comprehensive discussions that compare and contrast shared ideas in both compositions. Written in a lucid and concise fashion, this book offers new insights into the Gilgamesh Epic and Genesis 1-11 in an accessible way. "The Gilgamesh Epic in Genesis 1-11": Peering into the Deep is suitable for students and scholars of ancient Near Eastern literature, with broad appeal across religious studies, ancient history, and world literature